Еще раз об этнониме «трапезиты» - Катюшин, А.Е. (Материалы по археологии, истории и этнографии Таврии, 2005)
Византийский писатель VI в. Прокопий Кесарийский в IV главе своей книги “Война с готами” поместил сведения о готах-тетракситах, и его сообщение уникально - больше ни один источник не упоминает имени этого народа. Прокопий сообщает, что “рядом с теми местами, откуда начинается устье Болота (пролив Боспор Киммерийский - Е.К.), живут так называемые готы- тетракситы, они немногочисленны, и, тем не менее, не хуже многих других соблюдают христианский закон. A Byzantine author of the бth century, Procopius Caesarean wrote in his book “the War with the Goths” about the Goths - Tetraxites, living on the Asian part of Bosporus Cimmerian during his time. Procopius reports that in the second half of the 5th century the Huns -Utigurs met these people coming back from Eastern Europe to Eastern part of the Azov region through the Crimean peninsula and Bosporus Strait. Armed conflict between the Huns and Goths completed with peaceful agreement; as a result of it, the Utigurs and Tetraxites moved to the opposite part of the Bosporus Cimmerian together.